THE IMPACTS OF UNCERTAINTY ON BANKING SECTOR - ÇALIŞ, Mehtap; KAYA, Ferudun (Atlas Journal, 2021)
The power of banking sector, which constitutes a substantial part of financial system, is of importance in sustaining financial stability in long term. In this context, determining of the the banking sector’s performance is essential. One of the factors affecting the banking sector’s performance is uncertainty. This paper aims to exhibit how uncertainty influences the banking sector’s performance over the period of 2003:Q1-2020Q3. Using ARDL approach, it is inferred that capital adequacy, active quality and balance sheet have significant impacts of the performance in banking sector in both short and long terms. Uncertainty is determined to be a factor deteriorating the performance of the banks in both short and long terms. Finally, the imbalances occured in banking sector due to a shock are adjusted entirely after one period of time. The so-called results indicates that policy makers should produce the policies to eliminate the uncertainty for sustaining of financial stability.